“Análisis de la producción de largometrajes cinematográficos de la ciudad de Loja-Ecuador, periodo de estudios 2005-2018” - Poma Medina, Morelia Anabel (2019)
This research work was born with the purpose of giving life to the cinematographic memory of the city of Loja. That is why its content aims to provide knowledge, both academic and cultural to students and citizens, about the film productions made in the province of Loja. The present work has been able to verify the deficiency of antecedents and precise documentation on the history and analysis of the Loja cinematography production. For this reason, objectives were raised that seek mainly the knowledge of the most relevant feature films from 2005 to the present date. Achieving, this objective, through the review of different sources such as journalistic references in theses and other texts, in addition to the information provided by directors, producers, actors and specialists of lojano cinema. Accessing thus, to the analysis of the factors that have caused the break of the flow of the production of lojanas films. In this way, several communication methods are sought that can stimulate film entrepreneurship in the first instance, and above all, enhance the appreciation of foreign films in the citizenship. Thus, it was determined through the different sources, for example, the limitations that lojano cinema has from the personal perspectives of the filmmaker interviewed. They expressed, openly, the lack of support from the main public and private institutions in the financial… This can be seen in the limited production in recent years of Lojano cinema. Since this is not enhanced because of the centralization of funds that these institutions grant exclusively to the largest cities in the country among them; Quito, Guayaquil and Cuenca